Compensatory effects of individual differences, language proficiency, and reading behavior: an eye-tracking study of second language reading assessment - Tywoniw, Rurik (Frontiers in Communication, 2023)
Reading in a second language (L2) is a complex process that incorporates linguistic knowledge and literacy abilities, as well as strategic competence to approach different types of reading tasks depending on reading goals. However, much of the previous research was limited to correlational studies and focused on the relative contribution of broad categories of L2 proficiency and first-language (L1) literacy to L2 reading comprehension. However, investigations into L2 reading performance can benefit from advances in real-time, concurrent data collection methodologies such as eye-tracking. This study utilized eye-tracking methods to examined L2 reading comprehension of 102 readers across three different reading tasks [Cloze reading, Multiple-choice (MC) quiz, and reading-to-summarize], comparing the comprehension scores to L2 proficiency, individual differences (reasoning, working memory, motivation) and reading behavior (eye-tracking metrics related to attention to reading texts and tasks, length of fixations). Results indicate that the score on each task could be modeled each using a different mix of predictors, with the cloze task being most strongly predicted and the MC task being least predicted. The Summary task was in-between, but with a highly interpretable model. Interactions between fixation duration and cognitive abilities were found, showing how efficient fixation is generally important for comprehension, but the impact can be compensated for with motivation and reasoning ability.